2010
DOI: 10.1136/emj.2009.074211
|View full text |Cite
|
Sign up to set email alerts
|

Duration of mission time in prehospital emergency medicine: effects of emergency severity and physicians level of education

Abstract: The effect of education on treatment process and outcome in prehospital emergency care should merit further research, especially to ensure that junior emergency physicians are properly trained before they work in prehospital emergency medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Most dispatches occurred during daytime, especially in the afternoon. A German study reported a similar pattern, although their peak proportion of missions per hour was before noon 25. The summer is a busy period, probably because of more outdoor‐related activity, and the frequency of competing missions increased in these periods.…”
Section: Discussionmentioning
confidence: 71%
“…Most dispatches occurred during daytime, especially in the afternoon. A German study reported a similar pattern, although their peak proportion of missions per hour was before noon 25. The summer is a busy period, probably because of more outdoor‐related activity, and the frequency of competing missions increased in these periods.…”
Section: Discussionmentioning
confidence: 71%
“…However, these findings support the thesis that telemedically supported prehospital diagnosis and therapy on the whole is a safe procedure, although the process was completely new for the participating physicians as well as for the paramedics. In comparison with ground- or helicopter-based EMS physician operations [23], this concept allows for a spatially unrestricted emergency concept with fewer resources. At this point it has to be mentioned that, to our knowledge, most studies with 12-lead-ECG transmission represent rather small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include prehospital strategies,42 level of training of ambulance crews,43 and hospital capacity 44. Future studies should address the influence of these factors.…”
Section: Discussionmentioning
confidence: 99%